Struktur dan Fungsi Pantun Meminang dalam Pernikahan Masyarakat Melayu Di Kecamatan Semparuk Kabupaten Sambas - Srinita, Jesi; Fitri, Fitri; Mulyani , Sri (Innovative: Journal Of Social Science Research, 2024)
This research is to describe the structure and function of pantun with a structural approach. The sub-problems in this research include how the rhyme is structured, how the rhyme functions, and how to implement the research results into plans for implementing Indonesian language learning in schools. The method used in this research is descriptive. The form of this research is qualitative. The data source for this research is recordings of pantun meminang in Semparuk District. Data collection techniques in this research are non-participant observation techniques, structured interview techniques, and documentation techniques. Data collection tools in this research are observation guidelines, interview guidelines, and documentation. Techniques for analyzing data, namely the analysis stage, checking the validity of the data used include reading persistence, triangulation techniques, persistence/consistency in observations. Based on data analysis and discussion, it can be concluded that the structure and function of pantun meninang in the marriage of the Malay community in Semparuk District, Sambas Regency, with the results of the research, there are 31 pantun meninang, the physical structure of 31 pantun including diction, 18 pantun including imagery, 31 pantun including concrete words, 4 pantun including figurative language, 3 pantuns including rhyme, 7 pantuns including rhythm, 12 pantuns including themes, 11 pantuns including feelings, 9 pantuns including tone and atmosphere, and 31 pantuns including mandates. 2 rhymes include a recreational function, 2 rhymes include a didactive function, 15 rhymes include a morality function, 12 rhymes include a religious function. This research can be implemented in class VII, even semester, namely KD 3.14 Examining the structure and language of folk poetry (rhymes, verses and forms of local folk poetry) which are read and heard and K 4.14 Expressing ideas, feelings, messages in the form of folk poetry orally and in writing pay attention to structure, rhyme, and language use.